Genetic diversity and gene flow decline with elevation in montane mayflies - Polato, N. R.; Gray, M. M.; Gill, B. B.; Becker, C. G. [UNESP]; Casner, K. L.; Flecker, A. S.; Kondratieff, B. C.; Encalada, A. C.; Poff, N. L.; Funk, W. C.; Zamudio, K. R. (Nature Publishing Group, 2017)
Montane environments around the globe are biodiversity 'hotspots' and important reservoirs of genetic diversity. Montane species are also typically more vulnerable to environmental change than their low-elevation counterparts due to restricted ranges and dispersal limitations. Here we focus on two abundant congeneric mayflies (Baetis bicaudatus and B. tricaudatus) from montane streams over an elevation gradient spanning 1400 m. Using single-nucleotide polymorphism genotypes, we measured population diversity and vulnerability in these two species by: (i) describing genetic diversity and population structure across elevation gradients to identify mechanisms underlying diversification; (ii) performing spatially explicit landscape analyses to identify environmental drivers of differentiation; and (iii) identifying outlier loci hypothesized to underlie adaptive divergence. Differences in the extent of population structure in these species were evident depending upon their position along the elevation gradient. Heterozygosity, effective population sizes and gene flow all declined with increasing elevation, resulting in substantial population structure in the higher elevation species (B. bicaudatus). At lower elevations, populations of both species are more genetically similar, indicating ongoing gene flow. Isolation by distance was detected at lower elevations only, whereas landscape barriers better predicted genetic distance at higher elevations. At higher elevations, dispersal was restricted due to landscape effects, resulting in greater population isolation. Our results demonstrate differentiation over small spatial scales along an elevation gradient, and highlight the importance of preserving genetic diversity in more isolated high-elevation populations.